Impact of sorghum research and Development in Zimbabwe: The case of SV 2 - Anandajayasekeram, P.; Martella, D.R.; Sanders, J.; Kupfuma, B. (CAB International, 2007)
Sorghum and millet are important for human consumption in marginal rainfall regions, for low income consumers in other regions and for beer production in Zimbabwe. After independence the research and policy emphasis on sorghum shifted towards communal farmers, from red-seeded to the white-seeded sorghum varieties. The variety SV 2 was identified from an International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) regional trial in 1980 released in 1987 and subsequently commercialized by Seed Co-op, a private seed company. The diffusion of SV 2 was accelerated during the dry years of the 1990s. In this study an attempt was made to assess the impact of R&D investment on SV 2. Farm surveys indicated that in a normal year there were substantial yield gains from the introduction of SV 2 alone without and with the use of fertilizer. The benefits of the introduction of SV 2 are calculated with two different assumptions: with and without fertilizer. The estimated net present value for 10, 15 and 20% discount rate was positive indicating that the Development and transfer SV 2 generated benefits that are over and above the amount invested. The estimated internal rate of return was about 25%. The effect of use of fertilizer on IRR was modest. Sensitivity analysis indicated that omission of administration, overhead and depreciation costs, and the extended benefit flow period significantly affect the rate of return to technology Development and transfer.